Analysis of external conflict of the main character in the pound comic on webtoon - Adiguna, I Putu; Jayantini, I G A Sri Rwa; Resen, I Wayan (Institut Pariwisata dan Bisnis Internasional, 2022)
This study is to find out the types of external conflict faced by the main character in the pound comic on webtoon, and to handle the conflict with five style management strategies faced by the main character in the pound comic on webtoon. The data sources of this study were taken from webtoon. This study used a descriptive qualitative method. The data were analyzed based on the theory proposed by Kenney (1966), about types of conflict and the supporting theory proposed by Thomas and Kilmann (1970), about conflict management strategy. The result of this study showed the source of external conflict happened in the comic, there are man against man and man against society. The conflict also identified the strategy used by the main character in the pound comic on webtoon to handle the external conflict such as, competing, collaborating, compromising, accommodating, and avoiding.